Effect of dexmedetomidine on the minimum alveolar concentration of isoflurane in cats - Escobar, A. [UNESP]; Pypendop, B. H.; Siao, K. T.; Stanley, S. D.; Ilkiw, J. E. (Wiley, 2012)
This study reports the effects of dexmedetomidine on the minimum alveolar concentration of isoflurane (MAC iso) in cats. Six healthy adult female cats were used. MAC iso and dexmedetomidine pharmacokinetics had previously been determined in each individual. Cats were anesthetized with isoflurane in oxygen. Dexmedetomidine was administered intravenously using target-controlled infusions to maintain plasma concentrations of 0.16, 0.31, 0.63, 1.25, 2.5, 5, 10, and 20ng/mL. MAC iso was determined in triplicate at each target plasma dexmedetomidine concentration. Blood samples were collected and analyzed for dexmedetomidine concentration. The following model was fitted to the concentration-effect data: where MAC iso.c is MAC iso at plasma dexmedetomidine concentration C, MAC iso.0 is MAC iso in the absence of dexmedetomidine, I max is the maximum possible reduction in MAC iso, and IC 50 is the plasma dexmedetomidine concentration producing 50% of I max. Mean±SE MAC iso.0, determined in a previous study conducted under conditions identical to those in this study, was 2.07±0.04. Weighted mean±SE I max, and IC 50 estimated by the model were 1.76±0.07%, and 1.05±0.08ng/mL, respectively. Dexmedetomidine decreased MAC iso in a concentration-dependent manner. The lowest MAC iso predicted by the model was 0.38±0.08%, illustrating that dexmedetomidine alone is not expected to result in immobility in response to noxious stimulation in cats at any plasma concentration. © 2011 Blackwell Publishing Ltd.
Keywords: dexmedetomidine; isoflurane; animal experiment; concentration response; controlled study; drug blood level; drug potentiation; experimental cat; female; IC 50; minimum lung alveolus concentration; nonhuman; priority journal; Analgesics, Non-Narcotic; Anesthesia, Inhalation; Anesthetics, Inhalation; Animals; Cats; Dexmedetomidine; Dose-Response Relationship, Drug; Drug Interactions; Female; Isoflurane; Pulmonary Alveoli